2021
DOI: 10.1101/2021.02.15.431217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic association of IκBα to chromatin is regulated by acetylation and cleavage of histone H4

Abstract: IκBs exert a principal function as cytoplasmic inhibitors of the NF-kB transcription factors. Additional functions for IκB homologues have been described including association to chromatin and transcriptional regulatioin. Phosphorylated and SUMOylated IκBα (pS-IκBα) binds histones H2A and H4 in the stem and progenitor compartment of skin and intestine, but the mechanisms controlling its recruitment to chromatin are largely unstudied. We here show that serine 32-36 phosphorylation of IκBα favors its binding wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Finally, the findings reported here are coherent with the few common notions about histone clipping (Dhaenens et al , 2015): (i) Histone clipping is strongly associated with developmental transitions (Duncan et al , 2008; De Clerck et al , 2019; Ferrari et al , 2021); (ii) proteins that can cleave histones have all been known for very different functions and are most often not associated with nuclear localization; (iii) hPTMs might regulate the clipping (Duncan et al , 2008; Ferrari et al , 2021); and (iv) very plausibly, clipping is part of a complex regulatory system that has a lot of redundancy (Duncan et al , 2008; Dhaenens et al , 2015; Ferrari et al , 2021). This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021). However, one aspect of clipping is very different this time: Despite its dramatic nature, inhibition of clipping rarely inhibits cell transition (Duncan et al , 2008), yet in the current work (Marruecos et al , 2021) and in Ferrari et al, (2021), it is shown for the first time that trypsin inhibition can block intestinal differentiation effectively.…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationmentioning
confidence: 81%
See 3 more Smart Citations
“…Finally, the findings reported here are coherent with the few common notions about histone clipping (Dhaenens et al , 2015): (i) Histone clipping is strongly associated with developmental transitions (Duncan et al , 2008; De Clerck et al , 2019; Ferrari et al , 2021); (ii) proteins that can cleave histones have all been known for very different functions and are most often not associated with nuclear localization; (iii) hPTMs might regulate the clipping (Duncan et al , 2008; Ferrari et al , 2021); and (iv) very plausibly, clipping is part of a complex regulatory system that has a lot of redundancy (Duncan et al , 2008; Dhaenens et al , 2015; Ferrari et al , 2021). This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021). However, one aspect of clipping is very different this time: Despite its dramatic nature, inhibition of clipping rarely inhibits cell transition (Duncan et al , 2008), yet in the current work (Marruecos et al , 2021) and in Ferrari et al, (2021), it is shown for the first time that trypsin inhibition can block intestinal differentiation effectively.…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationmentioning
confidence: 81%
“…This redundancy is now also confirmed in intestinal differentiation, through either cathepsin L on H3 (Ferrari et al , 2021) or chymotrypsin on H4 (Marruecos et al , 2021). However, one aspect of clipping is very different this time: Despite its dramatic nature, inhibition of clipping rarely inhibits cell transition (Duncan et al , 2008), yet in the current work (Marruecos et al , 2021) and in Ferrari et al, (2021), it is shown for the first time that trypsin inhibition can block intestinal differentiation effectively.…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyte Differentiationmentioning
confidence: 81%
See 2 more Smart Citations
“…Based on the mechanistic similarities between regeneration and cancer, it is likely to speculate that IκBα may also play a relevant role in intestinal tumor initiation and/or progression. Recently, it was found that intestinal differentiation is linked to histone clipping, in particular of histone H3 [75] and H4 [76]. Loss of the N-terminal tail of H4 by action of trypsin and chymotrypsin leads to the release of IκBα from the chromatin, being dynamic chromatin binding/dissociation of IκBα required for proper differentiation of intestinal lineages.…”
Section: Iκ κ κBα α α Alterations In Other Solid Tumorsmentioning
confidence: 99%